2006
DOI: 10.2134/jeq2006.0038
|View full text |Cite
|
Sign up to set email alerts
|

Emission of the Greenhouse Gases Nitrous Oxide and Methane from Constructed Wetlands in Europe

Abstract: The potential atmospheric impact of constructed wetlands (CWs) should be examined as there is a worldwide increase in the development of these systems. Fluxes of N(2)O, CH(4), and CO(2) have been measured from CWs in Estonia, Finland, Norway, and Poland during winter and summer in horizontal and vertical subsurface flow (HSSF and VSSF), free surface water (FSW), and overland and groundwater flow (OGF) wetlands. The fluxes of N(2)O-N, CH(4)-C, and CO(2)-C ranged from -2.1 to 1000, -32 to 38 000, and -840 to 93 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
79
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(118 citation statements)
references
References 59 publications
18
79
7
1
Order By: Relevance
“…Recent studies showed that natural and artificial wetlands could be important emission sources of N 2 O (Wang et al 2006b;Søvik et al 2006). In this context, it is important to note that N 2 O has an atmospheric lifetime of 120 years and a global warming potential 296 greater than CO 2 (over a 100 year time horizon) and is anticipated to be responsible for about 5% of global warming.…”
Section: Potential Relationship To Nitrous Oxide (N 2 O) Emissionsmentioning
confidence: 99%
“…Recent studies showed that natural and artificial wetlands could be important emission sources of N 2 O (Wang et al 2006b;Søvik et al 2006). In this context, it is important to note that N 2 O has an atmospheric lifetime of 120 years and a global warming potential 296 greater than CO 2 (over a 100 year time horizon) and is anticipated to be responsible for about 5% of global warming.…”
Section: Potential Relationship To Nitrous Oxide (N 2 O) Emissionsmentioning
confidence: 99%
“…For example, constructed wetlands, lakes, and rice paddies are significant sources of N 2 O due to high nitrogen loading (Lilkanen and Martikainen 2003;Xu et al 2004;Sovik and Klove 2007). About N 2 O fluxes in wetlands, great spatial and temporal variation was found in many studies (Sovik et al 2006;Song et al 2008;Allen et al 2011;Jørgensen et al 2012). Several factors dominantly control N 2 O production, including soil moisture content, the standing water depth, plant growth pattern, O 2 availability, soil labile carbon, and nitrogen (Lilkanen and Martikainen 2003;Song et al 2008;Burgin and Groffman 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are many pathways by which the removed N can contribute to water and air pollution: accumulation and adsorption in soils, leaching of nitrate (NO to the atmosphere, and/or conversion to N 2 gas. Constructed wetlands significantly contribute to atmospheric N 2 O emissions either directly to the atmosphere from the surface of the wetland (IPCC, 2013;Søvik et al, 2006;Ström et al, 2007;Elberling et al, 2011) or indirectly via dissolved N 2 O in the effluent or groundwater upon discharge to surface waters. The IPCC (2013) has recognized the significance of indirect N 2 O emissions from CW effluent that is discharged to aquatic environments, and estimate emission factors (EF) ranging from 0.0005 to 0.25.…”
Section: Introductionmentioning
confidence: 99%
“…Anaerobic mineralization of organic C by methanogenic archaea can produce methane (CH 4 ) (Laanbroek, 2010;Ström et al, 2007;Søvik et al, 2006;Pangala et al, 2010). Constructed wetlands can also contribute to the dissolved organic carbon (DOC) load transfer to groundand surface waters, which may produce and exchange substantial amounts of CO 2 and CH 4 with the atmosphere (Clair et al, 2002;Elberling et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation